Pembelajaran Seni Rupa dalam Penerapan Kurikulum Merdeka di Sekolah Dasar - Iraqi, Hana Shilfia; Lena, Mai Sri; Sulastri, Juliana; Reviana, Fransisca Regy (YASIN, 2023)
Education certainly plays a very important role in preparing today's young generation for the next generation. The Ministry of Education and Culture has also launched several programs, one of which is the Mobilization School Program. This program creates a new curriculum called the Independent Learning Curriculum. In elementary school art education as well as in fine arts education, teachers need to explore simple basic procedures for creating fine art, because of course the teacher will teach elementary school students how to explore works of art and experiment with them to make art according to creativity. that each child has. The purpose of this study was to examine the independent curriculum in elementary schools in learning fine arts. The method used is a descriptive analysis method and a qualitative approach as well as observational data, and the results of interviews and documentation studies as data collection techniques. The results of this study relate to the planning and implementation of fine arts learning through an independent curriculum in the form of planning. making teaching modules and teaching module alignment for learning. Based on this information, it is determined how the independent curriculum will be implemented in terms of planning and delivery of learning.